PEGASO e-Diary: User Engagement and Dietary Behavior Change of a Mobile Food Record for Adolescents - Caon, Maurizio; Prinelli, Federica; Angelini, Leonardo; Carrino, Stefano; Mugellini, Elena; Orte, Silvia; Serrano, José C. E.; Atkinson, Sarah; Martin, Anne; Adorni, Fulvio (Frontiers in Nutrition, 2022)
Background Obesity amongst children and adolescents is becoming a major health problem globally and mobile food records can play a crucial role in promoting healthy dietary habits. Objective To describe the methodology for the implementation of the e-Diary mobile food record, to assess its capability in promoting healthy eating habits, to evaluate the factors associated with its usage and engagement. Methods This is a descriptive study that compared the characteristics of participants engaged in the e-Diary, which was part of the PEGASO project in which an app to provide proactive health promotion was given to 365 students at 4 European sites enrolled during October to December 2016: England (UK), Scotland (UK), Lombardy (Italy), and Catalonia (Spain). The e-Diary tracked the users’ dietary habits in terms of food groups, dietary indexes, and 6 dietary target behaviours relating to consumption of: fruit; vegetable; breakfast; sugar-sweetened beverages; fast-food; and snacks. The e-Diary provided also personalized suggestions for the next meal and gamification. Results The e-Diary was used for 6 months by 357 adolescents (53.8% females). The study showed that females used the e-Diary much more than males (aOR 3.8, 95%CI 1.6-8.8). Participants aged 14 years were more engaged in the e-Diary than older age groups (aOR 5.1, 95%CI 1.4-18.8) as were those with a very good/excellent self-perceived health status compared to their peers with fair/poor health perception (aOR 4.2, 95%CI 1.3-13.3). Compared to the intervention sites, those living in Catalonia (aOR 13.2 95%CI 2.5-68.8) were more engaged. In terms of behaviour change, a significant positive correlation between fruit (p<0.0001) and vegetables (p=0.0087) intake was observed in association with increased engagement in the e-Diary. Similarly, adolescents who used the app for more than 2 weeks had significantly higher odds of not skipping breakfast over the study period (aOR 2.5, 95%CI 1.0-6.3). Conclusions The users highly engaged with the e-Diary were associated with improved dietary behaviours: increased consumption of fruit and vegetables and reduced skipping of breakfast. Although the overall usage of the e-Diary was high during the first weeks, it declined thereafter. Future applications should foster user engagement, particularly targeting adolescents at high risk.